2002
DOI: 10.1063/1.1449532
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent phase evolution of polycrystalline Pb(Zr0.35Ti0.65)O3 thin films

Abstract: The structural and electrical properties of metalorganic chemical vapor deposition-grown Pb(Zr0.35Ti0.65)O3 thin films ranging in thickness from 700 to 4000 Å have been investigated. Cross-sectional scanning electron microscopy showed that these films are columnar, with grains extending through the thickness of the film. High-resolution x-ray diffraction showed that while the thickest films are tetragonal, with reflections corresponding to a-type and c-type domains, films thinner than 1500 Å are not. Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…This rhombohedral phase has previously been reported in similar MOCVDgrown PZT thin fi lms with composition in the bulk tetragonal PZT phase fi eld. [ 40 ] The effect of wafer bending on ferroelastic domain volume fraction is symmetric with respect to biaxial are determined by local stresses on each grain, the other kind of 90 ° domain wall switching ( a to c domain) is also possible and it is indeed observed inside the regions marked by red and magenta circles. Here the domains switch from in-plane (gray) to out-of plane (light or dark contrast) polarization directions.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This rhombohedral phase has previously been reported in similar MOCVDgrown PZT thin fi lms with composition in the bulk tetragonal PZT phase fi eld. [ 40 ] The effect of wafer bending on ferroelastic domain volume fraction is symmetric with respect to biaxial are determined by local stresses on each grain, the other kind of 90 ° domain wall switching ( a to c domain) is also possible and it is indeed observed inside the regions marked by red and magenta circles. Here the domains switch from in-plane (gray) to out-of plane (light or dark contrast) polarization directions.…”
Section: Resultsmentioning
confidence: 88%
“…The high density of grain boundaries and surface asperities [ 40 ] present in these nanocrystalline fi lms might be expected to pin ferroelastic domain walls. Domain wall pinning has been observed by others in measurements of the converse piezoelectric effect in thin fi lms.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the structural distortion increase with the decreasing size of the A-site cation and that ferroelectric properties are strongly affected by structural distortion [12]. The lattice spaces calculated from the (1 1 7) [13,14], and 146 kV/cm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although the strain in these films have not been studied in this research, it is felt that polycrystalline films show minimal stress compared to that of an epitaxial film. This is because the strain energy density is minimized in a polycrystalline film on account of the presence of grain boundaries which facilitate the alleviation of stresses to a great extent, in a relatively short time [12]. The AFM image revealed well-crystallized films with a very fine microstructure.…”
Section: Structural and Morphological Propertiesmentioning
confidence: 93%